Method for preparing super-hydrophobic layer on surface of aluminum alloy

By using laser cladding technology and alkali etching on the surface of aluminum alloy workpieces, superhydrophobic coatings with high mechanical properties are prepared, which solves the problem of insufficient mechanical properties of superhydrophobic coatings in the prior art, and achieves efficient and stable superhydrophobic properties on the surface of aluminum alloys.

CN119710682APending Publication Date: 2025-03-28UNIV OF JINAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510035569.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult to prepare superhydrophobic coatings with high mechanical properties, especially on the surface of aluminum alloy workpieces.

Method used

The laser cladding process is used to cladd the coating mixed powder of a specific composition on the surface of the aluminum alloy workpiece, and the superhydrophobic layer with high mechanical properties is formed by alkali etching and fluorosilane modification.

Benefits of technology

The mechanical properties of the superhydrophobic coating on the surface of aluminum alloy are significantly improved, including wear resistance and stability, and can maintain excellent superhydrophobic properties in a variety of environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710682A_ABST
    Figure CN119710682A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a super-hydrophobic layer on an aluminum alloy surface. The method comprises the following steps: 1) cleaning and drying the surface of an aluminum alloy workpiece on which the super-hydrophobic layer is to be prepared; 2) cladding coating mixed powder on the surface cleaned in the step 1) by using a laser cladding process to form a cladding layer; 3) polishing, cleaning and drying the cladding layer; 4) performing alkali liquor etching on the cladding layer to form a cladding layer with a surface texture; the method comprises the steps of (1) preparing a coating mixed powder, (2) cleaning and drying a workpiece obtained in the step (4), (3) cleaning and drying the workpiece obtained in the step (4), (6) conducting surface modification treatment on the workpiece cleaned and dried in the step (5), and (7) cleaning and drying the modified workpiece, and the coating mixed powder comprises, by mass, 15% of Si, 5% of Cu, 5t% of Mg, 2% of Mn and the balance Al.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a super hydrophobic layer on the surface of an aluminum alloy. Background Art

[0002] Compared with iron, aluminum is the metal element with the highest content in the earth's crust, that is, its reserves are extremely large. Although the current unit price of aluminum and aluminum alloys is still higher than that of iron and iron-carbon alloys (carbon steel or cast iron), its application prospects are higher than iron. Therefore, research on aluminum alloys is becoming more and more extensive.

[0003] Aluminum (density of pure aluminum is 2.7 g / cm³) and aluminum alloys are used in more and more fields because their density is lower than that of iron (density of pure iron is 7.86 g / cm³) and iron alloys. However, due to the relatively poor surface properties and mechanical properties of pure aluminum, aluminum alloys are generally used instead of pure aluminum in industrial applications. In some applications, higher requirements are placed on certain surface properties of aluminum alloy workpieces, such as the super-hydrophobic property of the surface of aluminum alloy workpieces, which is generally prepared on the surface of aluminum alloy workpieces in the form of a super-hydrophobic coating.

[0004] After aluminum alloy workpieces are prepared with super-hydrophobic coatings, they have shown great application potential in many important fields such as anti-icing and anti-corrosion due to their extraordinary surface properties. Such coatings can significantly reduce the adhesion of water droplets on the surface of aluminum alloys, thereby effectively preventing the occurrence of icing, which undoubtedly provides crucial technical support for key industries such as aerospace, transportation, etc. At the same time, its excellent anti-corrosion performance also provides a reliable guarantee for the long-term protection of metal materials.

[0005] The surface of a super-hydrophobic material refers to a material surface with a stable contact angle greater than 150° and a rolling contact angle less than 10°. The technology for preparing super-hydrophobic coatings is now very mature, but how to prepare super-hydrophobic coatings with higher mechanical properties needs further research. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a super-hydrophobic coating on the surface of an aluminum alloy having relatively good mechanical properties.

[0007] According to an embodiment of the present invention, a method for preparing a super-hydrophobic layer on an aluminum alloy surface is provided, the method comprising the following steps: 1) Cleaning and drying the surface of the aluminum alloy workpiece on which the super-hydrophobic layer is to be prepared; 2) using a laser cladding process to clad the coating mixed powder on the surface cleaned in step 1) to form a cladding layer; 3) Grind, clean and dry the cladding layer; 4) etching the cladding layer with alkaline solution to form a cladding layer with a surface texture; 5) Cleaning and drying the workpiece obtained in step 4); 6) Step 5) The cleaned and dried workpiece is subjected to surface modification treatment; 7) Clean and dry the modified workpiece; The coating mixed powder has the following components in terms of mass percentage: Si 15% Cu 5% Mg 5t% Mn 2% The balance is Al.

[0008] Optionally, the alkali solution is 8 g / L to 12 g / L NaOH solution.

[0009] Optionally, the alkali solution etching time in step 4) is 13.5 min to 17 min.

[0010] Optionally, in step 6), the surface modification treatment of the workpiece is performed by immersing the workpiece in a 2 wt % fluorosilane ethanol solution.

[0011] Optionally, the soaking time is 2h; After soaking, take out the workpiece and place it in a constant temperature drying oven at 120°C for 2 hours.

[0012] Optionally, the process parameters of laser cladding in step 2) are: The spot diameter is 4mm, the power of the laser used is 2500w, the scanning speed is 15mm / s, and the powder feeding speed is 6L / min.

[0013] Optionally, the thickness of the cladding layer is not less than 5 mm and not more than 9 mm.

[0014] Optionally, the cleaning in step 1) includes a mechanical polishing step, wherein the mechanical polishing is performed using sandpaper ranging from coarse to fine, so that the surface roughness of the workpiece on which the super-hydrophobic layer is to be prepared is not less than 3.2 μm.

[0015] Optionally, the cleaning step further includes the step of ultrasonically cleaning the workpiece using anhydrous ethanol after mechanical polishing, and the cleaning time is not less than 15 minutes.

[0016] Optionally, the sandpaper used for mechanical grinding is 400#, 800#, 1000#, 1500#, and 2000# sandpaper in order from coarse to fine.

[0017] The coating components used in the method for preparing a super hydrophobic layer on the surface of an aluminum alloy according to an embodiment of the present invention include Si, Cu, Mg, Mn and the remainder of Al, so as to form an Al-Si alloy, and then on the basis of the Al-Si alloy, Cu and Mg elements are incorporated, aiming to enrich and optimize the microstructure of the alloy, thereby significantly improving its mechanical properties. The two elements Cu and Mg mainly contribute to the formation of two important strengthening phases, θ-Al2Cu and Q-Al5Cu2Mg8Si6, inside the alloy, and these strengthening phases play a key role in improving the strength of the alloy. At the same time, adding an appropriate amount of Mn element to the aluminum silicon alloy can promote Al 15 The formation of Mn3Si2 phase, this phase structure also has a significant enhancement effect on the hardness and strength of the alloy. The formation of two metal phases is conducive to improving the wear resistance of the coating, so that the coating has relatively good wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM morphology image of the cladding powder (coating mixed powder) used to prepare the super-hydrophobic layer on the aluminum alloy surface in the embodiment of the present invention after being fully mixed under an electron microscope.

[0019] Figure 2 The morphology of the cladding layer prepared in the embodiment of the present invention under a scanning electron microscope is shown in FIG.

[0020] Figure 3 This is an electron microscope morphology of the super-hydrophobic surface prepared in an embodiment of the present invention.

[0021] Figure 4 The contact angle and sliding angle diagrams of the super-hydrophobic surface prepared in the embodiment of the present invention after etching for different times.

[0022] Figure 5 This is a graph showing the change in contact angle of the super-hydrophobic surface prepared in an embodiment of the present invention with wear distance.

[0023] Figure 6 Graph showing the relationship between the contact angle of the super-hydrophobic surface prepared in an embodiment of the present invention and the immersion time in a 5 wt % NaCl solution. DETAILED DESCRIPTION

[0024] The present invention is described in detail below in conjunction with the specific manufacturing process of preparing a super-hydrophobic surface on an aluminum alloy surface.

[0025] The aluminum alloy is 6061 aluminum alloy. For the convenience of comparative testing, the workpiece is 6061 aluminum alloy metal plate. For the convenience of description, the 6062 aluminum alloy metal plate is referred to as the substrate.

[0026] First, the substrate needs to be cleaned so that the prepared super-hydrophobic layer can be relatively reliably bonded to the substrate. The substrate needs to be cleaned by mechanical grinding, mainly polishing, so that its surface roughness is higher than 3.2 μm.

[0027] Accordingly, the surface of the substrate is polished to remove dirt and oxide film on the substrate surface. The substrate is selected as 6061 aluminum alloy, mainly because 6061 aluminum alloy itself has high strength, can withstand large loads, and can ensure the stability and safety of the structure. At the same time, it can maintain stable performance for a long time in harsh environments. In particular, 6061 aluminum alloy is currently a widely used aluminum alloy and is more representative.

[0028] The cladding powder is configured, that is, the configuration of the coating mixed powder for preparing the super hydrophobic layer. The coating mixed powder has the following components in terms of mass percentage: Si 15% Cu 5% Mg 5t% Mn 2% The balance is Al.

[0029] Weigh each component powder accurately one by one, and the powder should be at least fine powder (the particle size range of fine powder is 1~100μm, and submicron powder, nano powder and ultrafine powder can also be used). In order to obtain a sufficient mixed phase so that the crystal phase between the powders is uniform after the metallurgical state is formed based on cladding, it is necessary to mix the components evenly before laser cladding.

[0030] Accordingly, the weighed powders were sequentially put into a planetary ball mill for mechanical mixing to ensure that they were fully and evenly mixed together. During the ball milling process, a ball-to-material ratio of 5:1 was adopted, that is, the mass ratio of grinding balls to powders was 5:1, and the ball milling was continued for 5 hours.

[0031] After ball milling, a uniformly mixed cladding powder is obtained. In order to determine the mixing degree of the cladding powder, the microscopic morphology of the cladding powder is observed through the mixing state and the scanning electron microscope (SEM) is used for detection. The results are as follows: Figure 1 As shown. It can be clearly observed from the figure that the cladding powder after ball milling and mixing mainly shows spherical and nearly spherical appearance characteristics. This unique morphology greatly enhances the flow properties of the powder. On the basis of Al-Si alloy, Cu and Mg elements are cleverly incorporated to greatly enrich and optimize the microstructure of the alloy, thereby significantly improving its overall performance. These two elements mainly contribute to the formation of two crucial strengthening phases, θ-Al2Cu and Q-Al5Cu2Mg8Si6, inside the alloy. These strengthening phases play a key role in improving the strength of the alloy.

[0032] At the same time, adding an appropriate amount of Mn element to the aluminum-silicon alloy can promote Al 15 The formation of Mn3Si2 phase, this phase structure also has a significant enhancement effect on the hardness and strength of the alloy.

[0033] Furthermore, the cladding powder was prepared on the substrate by laser cladding. Specifically, the above alloy powder was clad on the surface of the 6061 aluminum alloy substrate by laser cladding process. YLS-4000 laser was used and coaxial powder feeding was adopted. The cladding process parameters were as follows: spot diameter was 4 mm, laser power was 2500 w, scanning speed was 15 mm / s, and powder feeding speed was 6 L / min.

[0034] The thickness of the cladding layer is not less than 5 mm and not more than 9 mm, preferably 7 mm ± 0.5 mm. The scanning electron microscope image of the surface morphology of the prepared cladding layer is as follows: Figure 2 shown.

[0035] For the convenience of comparison, after preparing the cladding layer, it is cut into samples, and the subsequent processing is to process the samples to determine the samples with basically the same cladding layer.

[0036] First, a CNC wire-cutting machine was used to precisely cut out multiple samples with a size of 10 mm × 10 mm × 17 mm. Furthermore, the samples needed to be cleaned before etching to obtain a super-hydrophobic surface, and the cleaning was also performed by mechanical grinding followed by cleaning.

[0037] Then, to remove dirt, oxide film and other impurities on the surface of the sample cladding layer, a series of sandpapers with different coarseness and fineness were used to polish the sample step by step from coarse to fine. Specifically, the samples were carefully polished in the order of 400#, 800#, 1000#, 1500#, and 2000# sandpaper to ensure the flatness and smoothness of the surface.

[0038] After grinding, the samples were further polished individually to further improve the surface roughness.

[0039] Subsequently, the sample is ultrasonically cleaned with anhydrous ethanol for 15 minutes to ensure that the impurities and stains remaining on the surface are completely removed. After cleaning, the sample can be blown dry with a simple hair dryer to avoid impurities remaining on the polished surface. It can also be dried in a drying oven.

[0040] Since it is only used for sample processing rather than industrial application, the etching solution can be prepared and used immediately. The specific operation is: take 10g of analytical grade NaOH, pour it into a container with 1L of distilled water, and stir with a glass rod until NaOH is completely dissolved in the distilled water to form a NaOH etching solution with a concentration of 10g / L for use in subsequent steps.

[0041] The samples were etched. First, the six prepared samples were marked as A0, A1, A2, A3, A4 and A5 in turn. Subsequently, these samples were placed in containers containing 25 ml of 10 g / L NaOH etching solution. During the etching process, the etching time of each sample was strictly controlled, which was 0 minutes for the A0 sample (i.e., no etching, as a control group), 5 minutes for the A1 sample, 10 minutes for the A2 sample, 15 minutes for the A3 sample, 20 minutes for the A4 sample, and 25 minutes for the A5 sample. This setting is intended to observe and analyze the effects of different etching times on the surface morphology and properties of the samples. After etching is completed, the samples are taken out and necessary cleaning and drying treatments are performed for subsequent characterization and analysis.

[0042] Modification treatment to form a super hydrophobic coating. First, the six samples that have been etched are immersed in a 2wt% fluorosilane solution one by one, and the immersion time is set to 2 hours. This step is intended to modify the sample surface through the immersion treatment of fluorosilane to enhance its hydrophobic properties. After the immersion is completed, the sample is taken out and placed in a constant temperature drying oven at 120°C for 2 hours of curing treatment.

[0043] During the curing process, the fluorosilane molecules will form a stable and uniform coating on the surface of the sample, further consolidating the modification effect. After the sample is cooled to room temperature in the drying oven, the modified sample is ultrasonically cleaned with anhydrous ethanol to remove impurities or uncured fluorosilane molecules that may remain on the surface. The cleaning time should be long enough to ensure thorough cleaning of the sample surface. After cleaning, the sample is dried to remove residual moisture on the sample surface. After drying, the contact angle of the six samples is immediately measured using a contact angle meter. By comparing the contact angles of the samples at different etching times.

[0044] Then, a super-hydrophobic surface mechanical durability test was conducted to evaluate the stability of the super-hydrophobic performance of sample A3 after modification. First, a 200 g weight was firmly attached to the back of sample A3 by an adhesive to ensure that the sample could be rubbed stably during the test.

[0045] Next, place the sample horizontally on a piece of 800# sandpaper, ensuring that the rough surface of the sandpaper is in close contact with the test surface of the sample, thereby effectively simulating the wear in actual use. Then, pull the sample on the sandpaper at a constant speed (1cm / s), returning to the origin after sliding 10cm each time, and define this round trip process as a complete friction period.

[0046] After completing a friction period, the contact angle of the sample surface is immediately tested and recorded using a contact angle meter. In order to fully evaluate the mechanical durability of the sample, the above friction and testing process needs to be repeated until the contact angle drops below 150°. By recording the number of friction periods and the corresponding contact angle changes, the stability of the superhydrophobic performance of the sample under mechanical wear can be intuitively evaluated, and data support can be provided for further optimization.

[0047] Finally, the stability of the super-hydrophobic surface of the sample was tested by immersing the sample in a 5 wt% NaCl solution for one hour, then taking it out of the NaCl solution and air-drying it for half an hour, then ultrasonically cleaning and drying it, and then measuring the contact angle. Repeat the above test process until the contact angle drops below 150°.

[0048] Performance Analysis: The cladding layer prepared by laser cladding shows its unique surface structure under the observation of scanning electron microscope. It is clearly visible that there are many different phase precipitates distributed on the surface of the cladding layer, and these precipitates show significant diversity in morphology, size and distribution. The existence of these phase precipitates not only greatly enriches the surface morphology of the cladding layer, but also brings it a more complex microstructure. The complex microstructure they form provides more contact points and support for the adhesion and stability of the superhydrophobic coating, thereby helping to improve the durability and stability of the superhydrophobic surface.

[0049] The samples prepared by laser cladding technology were placed on a 402MVD hardness tester for hardness testing. Specifically, the average hardness of the cladding layer was as high as 141.2HV, in sharp contrast to the hardness of the substrate, which was only 95.4HV. This data clearly shows that the hardness of the cladding layer has been significantly improved.

[0050] Figure 4The close relationship between etching time and contact angle (CAs) of the sample surface in a 10 g / L NaOH solution is clearly demonstrated. Without etching treatment, the contact angle of the sample is 68.5°, showing a certain hydrophilicity. However, with the gradual increase of etching time, the contact angle undergoes a significant change process. Especially in the early stage of etching, that is, in the period of 5 to 15 minutes, the contact angle increases rapidly from 117° to 158°. This change is mainly due to the gradual exposure of the hard phase during the etching process. However, when the etching time is further extended to 25 minutes, the contact angle begins to show a downward trend, dropping to 132°, which clearly reveals that excessively extending the etching time will have an adverse effect on the micro-nano structure of the sample surface, thereby affecting the surface superhydrophobic properties.

[0051] In the mechanical durability test of the superhydrophobic surface, a sandpaper wear test was used to conduct a rigorous evaluation. Figure 5 As shown in the figure, the super-hydrophobic surface after etching for 15 minutes showed excellent performance in the sandpaper wear test, and its maximum wear distance reached 190 cm. This data fully proves that the super-hydrophobic surface has excellent mechanical durability. The micro-nano structure of the super-hydrophobic surface is mainly composed of elemental Si, manganese-rich phase and magnesium-rich phase. These phases are intertwined to form a rough micro-nano structure. The roughness of this structure is crucial to the realization of super-hydrophobic performance because it provides enough support points for water droplets, making it difficult for water droplets to spread on the surface easily. In the sandpaper wear experiment, these reinforcing phases are like armor that can resist the grinding and erosion of sandpaper, so that the surface can better maintain its integrity when worn. It is the existence of these reinforcing phases that enables the super-hydrophobic surface to maintain its super-hydrophobic performance in long-term wear tests, showing strong mechanical durability and wear resistance.

[0052] In the stability test of the super-hydrophobic surface, the sample was immersed in a 5 wt% NaCl solution for 10 hours. The experimental results showed that the contact angle of the sample showed a significant downward trend during the immersion process. Specifically, at the beginning, the contact angle of the sample was as high as 158°, showing its excellent super-hydrophobic performance. However, after 10 hours of immersion, the contact angle decreased to 149°. Figure 6 As shown, although it still remains at a high level, the ions in the NaCl solution penetrate into the micro-nano structure of the superhydrophobic surface and the surface fluorosilane molecular layer is damaged, thereby increasing the surface energy and causing a decrease in the contact angle.

[0053] The super-hydrophobic surface prepared by the present invention performs well in terms of stability, durability and production efficiency, successfully solves the key problems of super-hydrophobic materials in practical applications, and injects new vitality into the research and application of super-hydrophobic materials.

Claims

1. A method for preparing a super hydrophobic layer on an aluminum alloy surface, characterized in that: The method comprises the following steps: 1) Cleaning and drying the surface of the aluminum alloy workpiece on which the super-hydrophobic layer is to be prepared; 2) using a laser cladding process to clad the coating mixed powder on the surface cleaned in step 1) to form a cladding layer; 3) Grind, clean and dry the cladding layer; 4) etching the cladding layer with alkaline solution to form a cladding layer with a surface texture; 5) Cleaning and drying the workpiece obtained in step 4); 6) Step 5) The cleaned and dried workpiece is subjected to surface modification treatment; 7) Clean and dry the modified workpiece; The coating mixed powder has the following components by mass percentage: Si 15% Cu 5% Mg 5t% Mn 2% The balance is Al.

2. The method according to claim 1, characterized in that The alkali solution is 8g / L-12g / L NaOH solution.

3. The method according to claim 1 or 2, characterized in that: In step 4), the alkali solution etching time is 13.5min~17min.

4. The method according to claim 1, characterized in that: In step 6), the surface modification treatment of the workpiece is performed by immersing the workpiece in a 2 wt % fluorosilane ethanol solution.

5. The method according to claim 4, characterized in that The soaking time is 2h; After soaking, take out the workpiece and place it in a constant temperature drying oven at 120°C for 2 hours.

6. The method according to claim 1, characterized in that The process parameters of laser cladding in step 2) are: The spot diameter is 4mm, the power of the laser used is 2500w, the scanning speed is 15mm / s, and the powder feeding speed is 6L / min.

7. The method according to claim 1 or 6, characterized in that: The thickness of the cladding layer shall not be less than 5 mm and not more than 9 mm.

8. The method according to claim 1, characterized in that The cleaning in step 1) includes a mechanical polishing step, wherein the mechanical polishing is performed using sandpaper ranging from coarse to fine, so that the surface roughness of the workpiece on which the super-hydrophobic layer is to be prepared is not less than 3.2 μm.

9. The method according to claim 8, characterized in that The cleaning step also includes the step of using anhydrous ethanol to ultrasonically clean the workpiece after mechanical grinding, and the cleaning time is not less than 15 minutes.

10. The method according to claim 8, characterized in that The sandpaper used for mechanical grinding is 400#, 800#, 1000#, 1500#, and 2000# from coarse to fine.